2020
DOI: 10.5603/imh.2020.0011
|View full text |Cite
|
Sign up to set email alerts
|

Is physical and psychological work stress associated with fatigue in Danish ferry ship employees?

Abstract: Background: Fatigue is a recognised risk factor for safety in seafaring. While always dangerous, fatigue in ferry shipping is especially hazardous as it may jeopardise passengers' safety. To counteract fatigue, knowledge on its determinants is important. Little, however, is known on the influence from physical and psychosocial work environment factors within ferry shipping. The aim of the study was to investigate the association between work stress in terms of physical stressors, perceived job demands and job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
(102 reference statements)
0
7
0
1
Order By: Relevance
“…Seafarers with more habitability-related complaints were more likely to report poor sleep [ 42 , 56 ]; worse mood [ 56 ]; greater anxiety and depression [ 56 ]; lower job-related affective wellbeing [ 33 ]; and greater fatigue [ 37 , 42 , 56 ]. Conversely, other studies found that perception of noise, vibration and movements did not influence emotional exhaustion or sleepiness [ 7 ] and disturbance by the physical work environment was associated with only one facet of fatigue (lack of energy) [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seafarers with more habitability-related complaints were more likely to report poor sleep [ 42 , 56 ]; worse mood [ 56 ]; greater anxiety and depression [ 56 ]; lower job-related affective wellbeing [ 33 ]; and greater fatigue [ 37 , 42 , 56 ]. Conversely, other studies found that perception of noise, vibration and movements did not influence emotional exhaustion or sleepiness [ 7 ] and disturbance by the physical work environment was associated with only one facet of fatigue (lack of energy) [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants frequently reported high job demands [ 37 ] which were perceived as a stressor [ 28 ] and associated with fatigue [ 37 , 61 ] and job dissatisfaction and intentions to leave the industry [ 63 ]. Job demands relating to environmental compliance (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…After full-text review, two additional studies were excluded because the seafarers predominantly did not sleep on board [ 14 , 15 ]. In addition, two studies were hand-selected (one of these studies included tests in a ship simulator [ 16 ], and the other had a participant number of only eight sailors [ 17 ]).…”
Section: Methodsmentioning
confidence: 99%
“…According to the Ministry of Manpower and Transmigration in based on data on work accidents recorded in Indonesia every day an average of 414 occupational accidents is 22.7% due to fatigue that is quite high. Where the determinants of work fatigue vary from factors of work environment that are inadequate to work (noise, lighting and temperature), rest periods and disproportionate working hours can increase the degree of work discharge, the health of workers who are not monitored properly, giving Inadequate nutrition can result in work fatigue, workload on workers should be adjusted to the physical and psychological abilities of workers, travel time to and from work, mental development that takes place periodically and work shifts [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Almost the same data can also be seen in a community survey in the UK which states that 25% of women and 20% of men complain that they always feel tired. Even though work fatigue is complained almost every day by workers in each work unit, but until 1990 work fatigue is still a mystery of the modern medical world which is full of obscurity in its causes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%